Modified Gorski-Popiel Technique and Synthetic Floating Transformer Circuit Using Minimum Components - Sagbas, Mehmet; Ayten, Umut Engin; Sedef, Herman; Minaei, Shahram (WORLD SCIENTIFIC PUBL CO PTE LTD, 2017)
The aim of this paper is proposing an alternative method to Gorski-Popiel Technique in realization of synthetic transformers. A new synthetic floating transformer (FT) circuit is also given. The proposed synthetic transformer circuit uses two current backward transconductance amplifiers (CBTAs), three resistors, and two grounded capacitors. The primary selfinductance, the secondary self-inductance, and the mutual inductance can be independently controlled and can be tuned electronically by changing the biasing current of the employed CBTAs. It has a good sensitivity performance with respect to tracking errors. A band-pass filter is also realized to test the performance of the proposed synthetic transformer circuit. The validity of the proposed synthetic transformer circuit is demonstrated by PSPICE simulations and experimental results.
Keywords: Modified Gorski-Popiel technique; synthetic transformer; mutually coupled circuits; current backward transconductance amplifier; active circuits; band-pass filter; MUTUALLY COUPLED-CIRCUIT; INDUCTANCE SIMULATION; PASS FILTER; REALIZATION; DESIGN; CONVERTER; CBTA; OTA; Computer Science; Engineering